2012
DOI: 10.2139/ssrn.2171202
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Hours Worked and Technology

Abstract: We study the relationship between hours worked and technology during the postwar period in the US. We show that the responses of hours to technological improvements have increased over time, and that the patterns captured by the SVAR are consistent with those obtained from an RBC model with a less than unitary elasticity of substitution between capital and labor. Data supports the hypothesis that the observed changes in the response of hours to a technology shock are attributable to changes in the magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 94 publications
0
6
1
Order By: Relevance
“…Supplementary Material. We also note that in contrast to our results, Cantore et al (2017) found σ to increase across the consecutive 30-year windows of the post-war US data, from about 0.2 to about 0.7. Their result, however, concentrates on the short-run variation in the data instead of long-run trends as it is based on estimations of a Real Business Cycle model with CES production and a non-smooth, autoregressive specification of factor-augmenting technical change.…”
contrasting
confidence: 99%
“…Supplementary Material. We also note that in contrast to our results, Cantore et al (2017) found σ to increase across the consecutive 30-year windows of the post-war US data, from about 0.2 to about 0.7. Their result, however, concentrates on the short-run variation in the data instead of long-run trends as it is based on estimations of a Real Business Cycle model with CES production and a non-smooth, autoregressive specification of factor-augmenting technical change.…”
contrasting
confidence: 99%
“…It is interesting to start from monetary policy disturbances. According to Cantore, Ferroni, and León‐Ledesma (), empirical evidence suggests that the LS is counter‐cyclical in response to such disturbances but theoretical DSGE models predict a pro‐cyclical LS. Based on the impulse response functions (IRFs) displayed in Figure , the LS in the JPT model is indeed pro‐cyclical.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, parsing the observed gyrations of the LS over five decades allows the present model to come closer to the data in terms of pinning down the LS response to a plethora of shocks. More specifically, Cantore, Ferroni, and León‐Ledesma () find that the LS is counter‐cyclical in response to monetary policy innovations in the data, whereas the New Keynesian model features a monetary policy transmission that is based on a pro‐cyclical LS. These authors argue that several model modifications fail to alter the latter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the statistical inference in SVAR depends on the treatment of hours worked (first differences versus levels). These findings have renewed the debate on the relative contributions of various shocks to the business cycle as well as led researchers in the SVAR literature to draw discernibly contrasting inferences (Cantore, Ferroni, & Leon-Ledesma, 2017; Cantore, Leon-Ledesma, McAdam, & Willman, 2014; Christiano et al, 2003; Francis & Ramey, 2005b; Gali & Rabanal, 2005).…”
Section: Introductionmentioning
confidence: 95%